Sexual behavior Predictors of Satisfaction in a Chinese Sample - Tao, Peng; Brody, S. (Wiley-Blackwell, 2011)
Previous multivariate research in Europe found that sexual satisfaction was associated directly with frequency of penile–vaginal intercourse (PVI) but inversely with masturbation and some aspects of non-PVI partnered sex. Aims: To examine the associations of sexual satisfaction in a sample from the People’s Republic of China, including not only frequencies of various sexual behaviors, but also frequencies of orgasm. Methods: Chinese industrial workers (N = 158, age over 24 years) completed the sexual satisfaction scale of the Multidimensional Sexuality Questionnaire (MSQ) and a short form of the Marlowe-Crowne social desirability scale, and provided details of the one month frequencies of engaging in, and having an orgasm from, PVI, masturbation, and non-PVI partnered sex. Main Outcome Measures: Multiple regression prediction of sexual satisfaction from age, social desirability responding, and in separate analyses, frequencies of the sexual behaviors or the corresponding orgasm frequencies. Results: For men and women, sexual satisfaction was associated with frequency of PVI and of PVI orgasm (the latter for women only), but not other sexual behavior or orgasm frequency. Similar results were obtained for the MSQ satisfaction scale and for a single satisfaction item. Conclusions: Despite cultural differences (and our smaller, less diverse sample), the positive prediction of satisfaction from only PVI (and in our sample of women, PVI orgasm) frequency—but not other sexual activities—was similar to that in a Swedish sample. Future research might also examine possible occasional avoidance of ejaculation by some Chinese men.